2018
DOI: 10.1021/acs.orglett.8b03099
|View full text |Cite
|
Sign up to set email alerts
|

A Trefoil Macrocycle Synthesized by 3-Fold Benzannulation

Abstract: A new trefoil-shaped molecular architecture consisting of three conjugated macrocycles was synthesized through an unprecedented 3-fold copper catalyzed [4 + 2] benzannulation. DFT calculations indicate that the most stable conformation of this trefoil macrocycle is D 3 -symmetric. In agreement with the calculated results, the trefoil macrocycle in single crystals exists as a pair of enantiomers with D 3 -symmetry and exhibits interesting honeycomb-like supramolecular structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 49 publications
(28 reference statements)
1
7
0
Order By: Relevance
“…The geometrical optimization result reveals that the average twist angles of 69.93° and 50.37° between pyrene and phenyls appear in 9 and 10 , while a small twist angle of 13.00° is featured for compound 7 . Furthermore, the strain energy is estimated to be 1.05 kcal/mol for 9 and 25.96 kcal/mol for 10 , which are consistent with the values for cycloparaphenylenes . The orbital energy level (Table S2) demonstrated that the frontier energy levels in compound 7 being lower than those in [3]­cyclo-1,8-pyrenes is probably due to the highly conjugated system in 7 .…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…The geometrical optimization result reveals that the average twist angles of 69.93° and 50.37° between pyrene and phenyls appear in 9 and 10 , while a small twist angle of 13.00° is featured for compound 7 . Furthermore, the strain energy is estimated to be 1.05 kcal/mol for 9 and 25.96 kcal/mol for 10 , which are consistent with the values for cycloparaphenylenes . The orbital energy level (Table S2) demonstrated that the frontier energy levels in compound 7 being lower than those in [3]­cyclo-1,8-pyrenes is probably due to the highly conjugated system in 7 .…”
Section: Resultssupporting
confidence: 77%
“…Crystal structure of macrocycle 9 : (a) top view and (b) side view. All hydrogen atoms and the butyl groups are omitted for clarity . Blue, C; red, O.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dimeric macrocycle TPEMC was obtained in satisfactory yields of 32% via oxidative homocoupling of 7 in a diluted solution at the concentration of 0.9 mM. Finally, treatment of TPEMC with Na 2 S in the solvent mixture of toluene and ethylene glycol methyl ether (EGME) successfully converted the butadiyne moieties into thiophene rings in a high yield of 81%. , …”
Section: Resultsmentioning
confidence: 99%
“…[10] Fori nstance,b yc arrying out aL ewis acid assisted tandem cycloaddition/retrocycloaddition, Miao et al accomplished multisite ethynylene benzannulation in ap henanthryleneethynylene macrocycle. [11] This work demonstrated that benzannulative transformation of ethynylene to 2,3-naphthalenediyl offers acompetent approach to producing polyarene macrocycles.M oreover,c onsidering the relative ease in synthesizing various arylene-ethynylene macrocycles,a swell as the good susceptibility of the resultant naphthalenediyl unit to oxidative dehydrogenation en route to PA Hs, [12] this ethynylene benzannulation reaction is deemed well worthy of further exploration for the bottom-up syntheses of PA H nanotubes.…”
Section: Introductionmentioning
confidence: 89%